Hydatid disease with pseudo-aneurysm formation of the descending thoracic aorta: a case report - Mushtaq, Ruqia; Rauf, Fatima; Hanif, Muhammad; Ameer, Aqsa (International Surgery Journal, 2021)
Cystic echinococcosis, also known as hydatid disease, rarely occurs in aorta. In this article, we report a rare case of pseudo-aneurysm of the lower descending thoracic aorta communicating with the hydatid cyst; surgical excision was performed with primary repair of aorta. This report emphasizes the need for early diagnosis of hydatid cyst with high index of suspicion in endemic areas, particularly if in the vicinity of a major vessel and aggressive investigations followed by subsequent early treatment before disabling and life-threatening complications occur.